Electromagnetically induced modification of metal optical properties - Feizollah, Peyman (Kansas State University, 2021)
The reflection of light from a metal film is among the most fundamental and well-understood effects in optics. If the film thickness is greater than the wavelength, reflection is explained in simple terms with the electromagnetic boundary conditions. For film thickness much less than the wavelength, reflection is incomplete and more exotic physical effects become possible. This is especially so if the light illuminating the film is pulsed at the femtosecond time-scale. In this work, a new phenomenon is proposed where few-femtosecond laser pulses temporarily modify a thin metal film's optical properties. By casting a pulsed standing-wave pattern across the metal surface, conduction electrons are redistributed to create temporary regions of partially enhanced or depleted density. This constitutes a temporary change to the conductivity of the metal, and thus, a change to the transmittance and reflectance of the film. In regions where the density is enhanced (depleted), the transmittance is decreased (increased). The process is possible because the period of action of the applied electric field is shorter than the relaxation time for the conduction electrons. An experiment is conducted that tests the concept by measuring the change in reflectance and transmittance for films with thickness ranging from 20-400 Angstroms. A pair of calibrated photodiodes are used to monitor the reflection and transmission modulation of the sample. The data is collected over many laser pulses and is averaged which cancels the random power fluctuation effects of the laser. Our findings show that the film's transmittance decreases only when the standing-wave pattern is present. In other words, the metal sample is found to be less transparent hence a ``better" conductor in the presence of the conditioning beams compared to when there is no standing wave on the sample. As the pulse length of the pattern is increased, or as the film thickness is increased, these changes disappear. To gain further insight, the Drude free-electron model is used to develop a theoretical description for the process, which qualitatively agrees with the observed changes in reflectance and transmittance.
Keywords: Ultrafast lasers; Condensed matter physics; EIM; Modifying metal optical properties